Analyzing Translation Strategy of Loneliness Song Lyric - Kriswesti, Rhematra; Afifulloh, M; Widyasari (Smart Edu Center, 2023)
The song Loneliness went viral after America's Got Talent gave it a Golden Buzzer for the performance of the song's owner, Putri Ariani. Behind the popularity of this song, there is a sad story that Putri experienced, such as being underestimated because of her physical limitations. In this case, a song lyric can have value and be able to attract attention if the choice of words is correct. As the function of lyrics and songs is to speak universally, they can express the contents of the creator's heart, and reflect the culture of various existing cultural diversity. Therefore, examining song lyrics can provide an academic narrative of the meaning contained therein. This research aims to explain the technique of translating English into Indonesian for the song Loneliness by Putri Arian. Using a theoretical approach to translation techniques from Newmark (1988) and Larson (1984), the song Loneliness was analyzed qualitative-descriptive. The results of research on the lyrics of the song Loneliness by Putri Ariani are the meaning of the song using adaptation techniques, semantic translation and the concept of lexical items.